2022
DOI: 10.1016/j.prro.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Postoperative Spine Malignancy: A Systematic Review and International Stereotactic Radiosurgery Society Practice Guidelines

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
11
1
Order By: Relevance
“…A 1-year LC rate of 94% with the addition of preoperative embolization exceeds the rates previously reported by studies demonstrating the benefits of SBRT after surgical decompression. 9,11-16 The significantly enhanced LC remained durable at 24 months postoperatively.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…A 1-year LC rate of 94% with the addition of preoperative embolization exceeds the rates previously reported by studies demonstrating the benefits of SBRT after surgical decompression. 9,11-16 The significantly enhanced LC remained durable at 24 months postoperatively.…”
Section: Discussionmentioning
confidence: 87%
“…With the development of SBRT, LC rates have significantly improved compared with treatment with conventional radiation therapy with estimates claiming that SBRT with surgery achieves 1-year LC rates as high as 85% to 90%. 9,11-16 Blakaj and Palmer et al 2 identified the ideal timing for adjuvant SBRT for spine metastases observing improved LC among patients receiving SBRT within 40 days postoperatively. Incidentally, in a multivariate analysis, preoperative embolization was associated with enhanced LC among patients treated with surgical decompression and adjuvant SBRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractionated SBRT is also more common in the postoperative spine SBRT literature as a strategy to limit toxicity and wound breakdown because a large surgical bed is typically incorporated in the clinical target volume (CTV). [17][18][19] Reducing the dose per fraction also mitigates the risk of vertebral compression fracture (VCF) 20 ; however, to maintain the ablative treatment intent, the total dose is escalated as the number of fractions increases. Finally, patients undergoing reirradiation may also be at an increased risk of radiation-induced myelopathy (RM) after 1-to 2-fraction SBRT, given that the risk of late adverse effects increases with the dose per fraction; therefore, more fractionated courses of SBRT are typically applied in these situations.…”
mentioning
confidence: 99%